Poverty in Italy Features and Drivers in a European Perspective. - Saraceno, Chiara (Policy Press, 2020)
Three leading sociologists examine Italy's regime of poverty and the frequently misunderstood context of familialism in this in-depth study. With analysis of poverty's roots and development and modern trends including the migrant 'new poor', it adds European perspectives for a better understanding of a persistent crisis.